Implementation of the S-O-R Framework in Analyzing Consumer Behavior on TikTok Platform Toward Repurchase Intention - Muhammad Adhie Putra Rivaldy; Afa Ahmad Yunus; Mochamad Rifky Rifaldi; Elfindah Princes (Universitas Muhammadiyah Jakarta, 2025)
This research explores how consumers behave on the TikTok Shop platform using the framework of Stimulus-Organism-Response (SOR); this is done to identify the influence of digital stimuli on repurchase intention. This study has the objective to examine how brand authenticity, influencer credibility, and social media engagement as external stimuli influence brand trust and customer satisfaction as internal responses, and how these, in turn, shape consumers’ repurchase intention on TikTok Shop. The study applies a quantitative explanatory method, with respondent data collected from 550 TikTok Shop consumers in the Jabodetabek area, an urban region with high digital engagement. PLS-SEM via SmartPLS was applied to analyze the data. The findings show that brand authenticity significantly affects both brand trust and customer satisfaction. However, influencer credibility and social media engagement do not show significant effects. Both brand trust and customer satisfaction positively influence repurchase intention. These results provide a bigger understanding of psychological mechanisms in social commerce and give ideas for digital marketers seeking to enhance consumer retention through authentic branding and trust-based strategies